Performance Optimization of ZnO QDs/F8BT Heterojunction-Based UV-Visible Photodetectors Using MoO xHole Transport Layer - Singh A.P.; Jit S. (My University, 2025)
This article investigates the effect of the MoOx hole transport layer (HTL) on the performance of a poly(9,9-dioctylfluorene-alcohol-benzothiadiazol) (F8BT) and ZnO colloidal quantum dots (CQDs) heterojunction-based ultraviolet-visible (UV-vis.) photodetector fabricated on indium-tin oxide (ITO) substrates. The performance of the conventional ITO/ZnO CQDs/F8BT/Ag (Device-1) structure is compared with that of the proposed ITO/ZnO CQDs/F8BT/MoOx/Ag (Device-2) structure. The MoOx HTL in the proposed device is used to enhance the hole transport and reduce the dark current by preventing electron injection from anode under reverse bias. On the other hand, the trapping of photogenerated electrons at the intrinsic defects of ZnO CQDs has been explored for enhancing the external quantum efficiency (EQE) beyond 100% by trap-assisted photomultiplication phenomenon. The maximum responsivity (R) , specific detectivity (D∗ ) , EQE, rise time (τ on), and fall time ( τ off) of Device-2 (Device-1) were obtained as 44 A/W (24 A/W), 6.5× 10^12 Jones ( 1.3× 1012 Jones), ∼ 14171% (7729%), 0.016 s (0.026 s), and 0.018 s (0.030 s), respectively, under -1 V bias voltage and 25- μ W /cm2 light intensity of 385-nm wavelength. Furthermore, the MoOx HTL in Device-2 introduced the self-biased feature of the photodetector with the maximum values of R ,D∗ , EQE, τ on , and τ off as ∼ 59 mA/W, 3.70× 1010 Jones, 18.98%, 0.012 s, and 0.017 s, respectively, under zero-bias operation and 25- μ W /cm2 intensity of 385 nm. © 1963-2012 IEEE.